Analysis Of Response Time In The Comprehensive Emergency Obstetric Neonatal Care (PONEK) Unit At Sultan Sulaiman Regional General Hospital In 2026 - Samsinar; Rahmad Gurusinga; Novita Br Ginting (JURNAL KESMAS DAN GIZI (JKG), 2026)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) remain significant challenges in Indonesian healthcare. The speed of medical intervention, or response time, in the PONEK unit is a critical factor in saving the lives of mothers and newborns. As a 24-hour PONEK service provider, Sultan Sulaiman Regional General Hospital must ensure that emergency response times meet established standards to prevent fatal complications. This study aims to analyze the implementation of response time in the Comprehensive Emergency Obstetric Neonatal Care (PONEK) unit at Sultan Sulaiman Regional General Hospital in 2025, examined through aspects of human resource availability, competence, shift distribution, and specialist coordination. This research employs a descriptive qualitative method. Data collection was conducted through in-depth interviews with key informants (ER doctors, PONEK midwives, nurses) and triangulation informants (Head of Medical Services, Head of PONEK). Data analysis was performed thematically to provide an in-depth overview of the supporting and inhibiting factors of response time. The study identified that response time is influenced by the availability of 24-hour on-call specialists, the number of team members on each shift, and the effectiveness of coordination between the ER and the PONEK unit. Identified obstacles include unbalanced workloads at certain times and the need for regular competency training updates for the PONEK team.